Realism for the post-truth era: politics and storytelling in recent fiction and autobiography by Salman Rushdie. (4th May 2019) - Hoydis, Julia
ABSTRACT: This essay analyses Rushdie's novel The Golden House and his memoir Joseph Anton to explore entanglements between fact and fiction, raising questions about the perception and use of realism and postmodernism as aesthetic categories and narrative modes in twenty-first-century literature. At the centre of both texts are concerns with identity, politics, mystery, deception and revelation in what is referred to as the 'post-truth' era – ushered in by the 'Rushdie affair'. The argument focuses on the pursuit of truth and interplay of genres in Rushdie's texts which employ a mode of storytelling best described as a kind of 'operatic realism'.